(untitled) - Fowler, Susan L. (London, 2004)
Web Application Design Handbook is a panoramic book covering a lot of territory from how to design graphical user interfaces for Web applications to a discussion on the types of information visualization that are possible ... it provides a good overview on the techniques used to create Web applications, especially helpful for the novice Web designer who is tasked with building useful and effective Web applications
Keywords: Web site development,Web sites,Application software,Phát triển trang web,Phần mềm ứng dụng